2013 Ieee Sensors 2013
DOI: 10.1109/icsens.2013.6688502
|View full text |Cite
|
Sign up to set email alerts
|

Titanium nitride (TiN) as a gate material in BiCMOS devices for biomedical implants

Abstract: Titanium nitride (TiN) is a proven bio-compatible conductor and as such increasingly applied as an microelectrode material in novel biomedical devices. This paper reports the functioning of BiCMOS devices with titanium nitride as a gate electrode and interconnect material all fabricated in five photolithographic steps. This simple BiCMOS process allows the on-chip integration of a biomedical electrode arrays with electronics to reduce the electrode wiring density and hence reduce the electrodes footprint. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…In another study, Lawand et al validated the successful integration of TiN as a bio-compatible conductor in BiCMOS devices, allowing for the electrical integration of high-density biomedical electrode arrays on a single chip, which is especially important for devices like cochlear implants where space is limited. 243 Recently, Roberlo and coworkers deposited TiN thin films on AISI 316L stainless steel substrates using DC unbalanced magnetron sputtering, and they found that the TiN coatings exhibited promising characteristics, such as wear and corrosion resistance, making them suitable for biomedical applications. 244 The coatings exhibited improved performance in scratch tests using a biomaterial pin, simulating body fluids, indicating potential durability and suitability for implants.…”
Section: Biomedical Implantsmentioning
confidence: 99%
“…In another study, Lawand et al validated the successful integration of TiN as a bio-compatible conductor in BiCMOS devices, allowing for the electrical integration of high-density biomedical electrode arrays on a single chip, which is especially important for devices like cochlear implants where space is limited. 243 Recently, Roberlo and coworkers deposited TiN thin films on AISI 316L stainless steel substrates using DC unbalanced magnetron sputtering, and they found that the TiN coatings exhibited promising characteristics, such as wear and corrosion resistance, making them suitable for biomedical applications. 244 The coatings exhibited improved performance in scratch tests using a biomaterial pin, simulating body fluids, indicating potential durability and suitability for implants.…”
Section: Biomedical Implantsmentioning
confidence: 99%
“…2i. It has also been shown that TiN can be used as metallisation for a BiCMOS process [4], which can simplify the process. The would mean replacing the metallisation of the BiCMOS with TiN.…”
Section: Polymer Based Cochlear Implantmentioning
confidence: 99%
“…Two advantages of using TiN as the electrode material in neural implants are (1) its capacitive charge transfer with no irreversible reactions at low charge injection limits [11], and (2) because it is widely used in complementary metaloxide semiconductor (CMOS) circuitries [12]. By taking advantage of the use of TiN in the CMOS industry [13], integrated neural implants can be designed with local signal conditioning, wireless communication and other electrical modalities.…”
Section: Introductionmentioning
confidence: 99%